Participatory Learning of Medical Students through Development of Innovative Training Modules for Community Health Workers - Ramesh Bogam, Rahul; Saoji, Vivek; Sahasrabudhe, Ranjana; Saoji, Apoorva (International Journal of Medical Students, 2016)
Background: Community Medicine is a subject which receives relatively less attention in medical curriculum. Active participation of students in preparation of training modules for Community Health Workers (CHWs) could facilitate their learning in topics related to Community Medicine. This study aimed to involve medical students in the preparation of training modules for CHWs and assess the effects of their participation on their knowledge about targeted diseases. Methods: An interventional study where all 144 undergraduate fifth-semester students from Bharati Vidyapeeth University Medical College, Pune, India posted at Community Medicine Department participated in the preparation of training modules for CHWs on HIV/AIDS, tuberculosis, malaria and diabetes and completed pre- and post-intervention questionnaire. Each completed questionnaire was assigned a score based on a marking system. The data was analysed using paired t test. Results: Statistically significant improvement in knowledge was found (pre-test mean score: 5.79, post-test mean score: 14.15, t = 26.93, p<0.001). All faculty opined that community visits followed by health education module preparation activity were innovative components in this study. All 119 participants agreed that their knowledge about targeted diseases improved due to module preparation activity. Conclusion: Active participation of students can facilitate their learning behavior. Students became aware of the principles of ‘Group Dynamics’ as a result of active involvement in training module preparation.